Analisis Pengaruh Kecenderungan Manajemen Laba: Studi Empiris Pada Perusahaan Logistic - Siska Amonalisa Silalahi; Marwin Antonius Rejeki Silalahi (Institut Transportasi dan Logistik Trisakti, 2020)
Investors often see financial report of logistics companies only from one side such as profit - loss report. They assume that profit - loss report presented by the companies are real. The management of the companies know about that and they tend to do profit management in financial report. There are three important problems in the companies, there are investment decision, funding decision, and a policy to propose how much dividend should be distributed to shareholders. For that reason, the purpose of this research is to analyse about institutional ownership, managerial ownership, dividend policy, and debt policy towards profit management in logistics companies. The result of this research used statistical analysis by linear regression analysis. The data shows that institutional ownership, managerial ownership, and debt policy do not have an influence on management profit while dividend policy has significant effect in management profit. It signifies that if the companies do profit management, the company will do income decreasing that will be effect to dividend policy where the owner will get smaller dividend than they should get or the owner will decide to hold the existing profit and use it for investment. This is in accordance with keagenan theory.